Artifact on MR imaging by a dental magnetic attachment keeper: Preliminary study on a new keeper removable phantom. Issue 1 (27th March 2019) - Ogura, Ichiro; Sugawara, Yoshihiro; Nagata, Kazuhiro; Watanabe, Mitsuhiro
Abstract: Aims: Dental magnetic attachments with satisfactory retentive force and stability are now commercially available for dental treatment. The aim of this study was to investigate a new phantom for evaluation of the artifact on magnetic resonance (MR) imaging by a dental magnetic attachment keeper. Material and Methods: We developed a new keeper removable phantom for evaluation of the artifact on MR imaging. A keeper was inserted in an acrylic pole in a PET bottle. The keeper from acrylic pole of the phantom was removable. The keeper with saline solution in the PET bottle with a head and neck coil underwent MR imaging at our university hospital. We measured the real size (unit: mm) of artifact of the phantom with the keeper using a DICOM viewer. Furthermore, the size of artifact of a patient's image with the same three keepers in the mouth was measured on the image using the DICOM viewer, too. Results: In MR images of the phantom with a keeper, the maximum size of artifact on axial T1‐weighted, T2‐weighted and STIR images were 78 mm, 85 mm, and 67 mm, respectively. Regarding MR images of the patient with three keepers, the maximum size of artifact on axial T1‐weighted, T2‐weighted and STIR images were 106 mm, 111 mm and 100 mm, respectively. Conclusions: We investigated a new keeper removable phantom for evaluation of the artifact on MR imaging. The phantom can be used to evaluate the artifact on MR imaging by a dental magnetic attachment keeper.